2012
DOI: 10.1177/1359105312455077
|View full text |Cite
|
Sign up to set email alerts
|

Developmental contexts and sense of coherence in adolescence: A systematic review

Abstract: The salutogenic model has led to revolutionary changes in the study of health. In recent years, a large amount of research has been carried out on the relationship between sense of coherence and health, but relatively little is known about sense of coherence in adolescence. This study is a systematic review of the studies that looked at sense of coherence in adolescent samples. Valuable information is provided regarding the characteristics of the samples, the reliability of the sense of coherence scale version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 73 publications
5
62
0
4
Order By: Relevance
“…Most of Antonovsky's questions about SOC as an independent variable have now been answered. Seminal reviews have now documented ample evidence about the significant associations of SOC with wellbeing and quality of life Lindström, 2006, 2007), also in adolescence (Rivera et al, 2013). The issue of causality remains though, albeit that some longitudinal studies have provided some evidence (Suominen et al, 2001).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of Antonovsky's questions about SOC as an independent variable have now been answered. Seminal reviews have now documented ample evidence about the significant associations of SOC with wellbeing and quality of life Lindström, 2006, 2007), also in adolescence (Rivera et al, 2013). The issue of causality remains though, albeit that some longitudinal studies have provided some evidence (Suominen et al, 2001).…”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Numerous studies over recent decades have provided evidence of SOC's positive contributions to wellbeing and quality of life in general populations Lindström, 2006, 2007). Whilst less research has being carried out amongst young people (Rivera et al, 2013), there is some evidence that has shown similar associations between higher levels of SOC and significant positive outcomes such as greater subjective wellbeing (García-Moya et al, 2013c;Mosknes et al, 2013).…”
Section: Salutogenesis and Explanationmentioning
confidence: 99%
See 3 more Smart Citations